Effect of Fluoride, Casein Phosphopeptide-Amorphous Calcium Phosphate and Casein Phosphopeptide-Amorphous Calcium Phosphate Fluoride on Enamel Surface Microhardness After Microabrasion: An In Vitro Study - Ghazaleh Ahmadi Zenouz; Fariba Ezoji; Seyede Anese Enderami; Soraya Khafri (Tehran University of Medical Sciences, 2016)
Objectives: This study aimed to assess the effect of applying casein phosphopeptide-amorphous calcium phosphate (CPP-ACP) paste, casein phosphopeptide-amorphous calcium phosphate fluoride (CPP-ACPF) paste and sodium fluoride gel on surface microhardness of enamel after microabrasion. Materials and Methods: Thirty freshly extracted human premolars were selected. All samples were subjected to hardness indentations made with the Vickers hardness machine and the average value was recorded as the initial surface microhardness. The specimens were then randomly divided into three groups (n=10) of CPP-ACPF, fluoride and CPP-ACP. The teeth were micro-abraded with Opalustre. Microhardness test was performed to assess the post-abrasion hardness. Three remineralization modalities were performed on samples of each group. The enamel surface microhardness measurements were performed. To compare the difference between groups, the rehardening and softening values were defined. One-way ANOVA and Tukey's post hoc test at a significance level of 5% were used for statistical analysis. Results: The mean microhardness value (MMV) had a significant decrease after microabrasion from baseline. The MMV had a significant increase after remineralization in all groups. The MMV of CPP-ACPF group was significantly more than that of fluoride group (P=0.027). The rehardening value of fluoride group was significantly more than that of other groups (P<0.001). Conclusion: All the remineralizing agents were effective for rehardening the enamel after microabrasion. The CPP-ACP and CPP-ACPF pastes are effective, but to a lesser extent than neutral sodium fluoride gel in remineralizing enamel surface. Incorporation of fluoride to CPP-ACP formulation does not provide any additional remineralizing potential. Keywords: Casein phosphopeptide-amorphous calcium phosphate nanocomplex; Enamel Microabrasion; Hardness; Sodium Fluoride